El derecho a la educación limitado a los trabajadores mayores de edad regulados por el Código de Trabajo. - Pazos Ledesma Jenny Gabriela (2024)
The right to Education or the right to Vocational Training that workers have, includes an inalienable and inviolable right in the Rule of Law in which Ecuador finds itself, since, in the productive dimension, work is the fundamental pillar of economic development, which is complemented by the level of professionalism and training of the human talent that is under an employment relationship. That is why; achieving a balance between work and study is fundamental for a developing State, since; training or study comprises a dimension of employment strategy; as well as; an indicator of economic growth. Currently, the existing labor legislation limits the right to education of all those workers of legal age who are regulated by the Labor Code, since there is no legal provision that allows the productive force to access a permit or license to exercise their right to education or vocational training. That is why research is fundamental to make this violation of rights visible and to establish a legal reform to the labor code, so that this regulatory body inserts provisions that favor the promotion of workers' education, as the Organic Law of the Public Service contemplates and that there is no positive discrimination between public sector workers and private business sector workers in the country. Applying as a research strategy a methodology with a descriptive approach, together with the application of an analytical scope, based on documentary analysis and qualitative-quantitative data collection. To meet the main objective and analyze the facilities that employers provide their workers to fulfill the right to Education.